The Role of Sufism in Countering Extremism: A Diplomatic Perspective - Khan, Dr. Assad Mehmood (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Sufism, as a mystical dimension of Islam, has historically emphasized peace, tolerance, and spiritual introspection, making it a potent ideological counterforce against extremism. This research explores the role of Sufism in countering extremism from a diplomatic perspective, analyzing how governments and international organizations incorporate Sufi traditions and networks into their counterterrorism and soft power strategies. Using a qualitative approach, the study examines case studies from regions where Sufi influence has been instrumental in fostering interfaith dialogue, deradicalization efforts, and community resilience. The research applies constructivist international relations theory to explain how Sufi traditions shape diplomatic narratives and policy frameworks. By assessing diplomatic initiatives that leverage Sufism in countering violent extremism (CVE) programs, this study highlights both the opportunities and challenges of integrating religious soft power into global security strategies. The findings suggest that while Sufi networks offer an alternative discourse to extremist ideologies, geopolitical constraints and sectarian tensions may limit their effectiveness. This research contributes to the broader discourse on religion and diplomacy, emphasizing the intersection of faith-based narratives and international relations in addressing security challenges.